A Wesleyan holiness theology and language world: a demonstration of holiness theology as a religious linguistic characteristic in the light of speech act theory. Issue 4 (July 2019) - Cho, Anna
Holiness as the subject of Wesleyan holiness theology is not only God's divine language but also an experiential language of humans. Despite this fact, research that considers the religious linguistic features of holiness theology as they relate to its meaning and effects in the real lives of believers seems to have been neglected. Thus, this article proposes to examine the language of holiness in terms of Wesleyan holiness theory by means of speech act theory. First, this approach solves the problem of overcoming the proposition principle of holiness theology. Second, it shows an understanding of the linguistic hermeneutics of the work of the Holy Spirit in believers. And finally, it presents the ways in which the religious divine language of holiness can be described as an ethical language characteristic of human experiential language.